2022
DOI: 10.1111/cob.12521
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Enhanced glucose availability and insulin resistance enhances an activated immune system and accounts for the obesity paradox

Abstract: Summary Many studies have demonstrated an ‘obesity paradox’ where people with obesity have reduced mortality in the context of acute critical illnesses compared to people of normal weight. In contrast, obesity is associated with reduced life expectancy in the population in general and is associated with an increased risk for type 2 diabetes, cardiovascular disease and other health problems. However, the absence of the metabolic syndrome is associated a lower mortality than when the metabolic syndrome is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Previous experiments have shown that glucose prioritizes the immune system’s needs, sustains macrophage viability, and slows disease development ( 35 ). The other factor is insulin resistance, which limits the quantity of glucose that non-obligate glucose consumers can metabolize while increasing the production of glycerol and fatty acids through the fat pool as an alternate fuel source for tissues and cells ( 36 ). Although it is not clear whether IR is involved in the stroke-obesity paradox, IR theoretically contributes to this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that glucose prioritizes the immune system’s needs, sustains macrophage viability, and slows disease development ( 35 ). The other factor is insulin resistance, which limits the quantity of glucose that non-obligate glucose consumers can metabolize while increasing the production of glycerol and fatty acids through the fat pool as an alternate fuel source for tissues and cells ( 36 ). Although it is not clear whether IR is involved in the stroke-obesity paradox, IR theoretically contributes to this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the immune response (equivalent to the hyper inflammatory state of sepsis) in healthy adults results in a metabolic rate increase of 37-55% [4] which is equivalent to about 175-261 g of glucose because the immune system substantially uses glucose [5]. Core temperature also increases.…”
Section: The Hyper Inflammatory Phase Of Sepsismentioning
confidence: 99%
“…A negative of glycolysis is that it is unable to produce sufficient ATP on an ongoing basis for all the cells of the normal healthy organism. It is only a temporary measure for the urgent need to produce large amounts of ATP for immune cells to destroy pathogens quickly in relatively anaerobic or ischaemic tissues [5,12].…”
Section: The Hypo Inflammatory Phase Of Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…The bodies of people with DM do not produce enough insulin, which is responsible for lowering blood sugar levels . If diabetics are not treated, their blood glucose levels may increase significantly, , and this may lead to kidney failure, cardiovascular disease, blindness, and impaired wound healing. α-Glucosidase (EC 3.2.1.20) is a carbohydrate-hydrolyzing enzyme, and its catalytic activity, as an intestinal digestive enzyme, results in cleavage of poly- and disaccharides into monosaccharides (glucose), which in turn will raise blood sugar levels. , Therefore, several α-glucosidase inhibitors (AGIs) such as acarbose, voglibose, miglitol, and nojirimycin are widely used alone or in combination with insulin injection as treatment of diabetes.…”
Section: Introductionmentioning
confidence: 99%